Indisciplina no contexto escolar: um estudo das significações abstraídas por estudantes brasileiros do ensino fundamental e médio - Vasconcelos, Mário Sérgio [UNESP]; Bellotto, Maria Elvira (My University, 2010)
This research has as main objective to identify the meanings which students of schools and high schools attribute in front of a conflict involving the indiscipline in school context. The theoretical and methodological reference used was the Theory of Thinking Organized Models. Organized Models are mental representation elaborated about a certain situation, compound by detached elements detached by the subject, the meanings attributed to these elements and the implication established between the elements and the meanings. To achieve our objective we researched the models abstracted by 100 students from 8, 10, 12, 14 and 16 years old (20 in each group of age), who attended two public schools in Assis (SP), Brazil. They are students of both gender, from second, fourth, sixth and eighth grade of schools and second grade of high school, chosen at random. To collect the data we used an interview and a presentation of two hypothetical conflicts related to an indiscipline situation inside classroom. The main conclusions were: a) almost all the participants (91%) disapproved the undisciplined acts; b) the major participants (88%), direct or indirect, approve the punishment to the author of the indiscipline; c) the representation are frequent with the meaning in a way to avoid the undisciplined act (68%); d) the meanings, in a way to avoid the undisciplined act, appear in a crescent way in a model presented by students from higher grades mainly in eighth grade from school and second grade from high school; e) the variety of organized models identify evidences, for beyond the cognitive aspects, the importance of affective and socialcultural in construction of arguments related to the moral judgment at school.

Essa pesquisa descritiva teve como principal objetivo identificar significações que alunos do ensino fundamental e médio atribuem diante de um conflito envolvendo a indisciplina em contexto escolar. O referencial teórico-metodológico utilizado foi a Teoria dos Modelos Organizadores do Pensamento. Modelos organizadores são representações mentais elaboradas sobre uma determinada situação, compostos pelos elementos destacados pelo sujeito, os significados atribuídos a esses elementos e as implicações estabelecidas entre os elementos e os significados. Para atingir nosso objetivo investigamos os modelos abstraídos por 100 alunos de 8, 10, 12, 14 e 16 anos (20 em cada grupo de idade), pertencentes a duas escolas públicas da cidade de Assis (SP), Brasil. São alunos de ambos os sexos, das 2a, 4a , 6ª e 8ª série do ensino fundamental e 2ª série do ensino médio, escolhidos aleatoriamente. Para coletar os dados utilizamos a entrevista e a apresentação de dois conflitos hipotéticos relacionados a uma situação de indisciplina em sala de aula. As principais conclusões foram: a) quase todos os participantes desaprovam os atos indisciplinados (91%); a maioria dos participantes (88%), direta ou indiretamente, aprova a punição para o autor da indisciplina; c) são freqüentes as representações no sentido de evitar a incidência do ato indisciplinado (68%); d) as significações, no sentido de evitar o ato indisciplinado, aparecem de forma crescente nos modelos apresentados por alunos das séries mais elevadas, principalmente da 8ª série do ensino fundamental e da 2ª série do ensino médio; e) a variedade de modelos organizadores identificados evidencia, para além dos aspectos cognitivos, a importância dos conteúdos afetivos e socioculturais na construção dos argumentos relacionados a julgamentos morais na escola.
Indiscipline in school context: a study about the meanings attributed by students of brazilian basic schools, schools and high schools
Keywords: School indiscipline; Thinking organized models; School and high school; Indisciplina Escolar; Modelos Organizadores do Pensamento; Ensino Fundamental; Ensino Médio